2021
DOI: 10.3390/foods10081945
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Extra Virgin Olive Oil Quality under Different Storage Conditions

Abstract: The extent and conditions of storage may affect the stability and quality of extra virgin olive oil (EVOO). This study aimed at evaluating the effects of different storage conditions (ambient, 4 °C and −18 °C temperatures, and argon headspace) on three EVOOs (low, medium, and high phenols) over 18 and 36 months, analyzing the main metabolites at six time points. The results showed that low temperatures are able to maintain all three EVOOs within the legal limits established by the current EU regulations for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 56 publications
4
32
1
Order By: Relevance
“…The extra virgin olive oil (EVOO) is a typical food in which the extent and conditions of storage may affect its stability and quality. Mousavi et al [ 19 ] evaluated the effects of different conditions of storage (ambient, 4 °C and −18 °C temperatures, and argon headspace) on three EVOOs (with low, medium and high phenol contents) over 18 and 36 months, through the analyses of the main metabolites at six time points. The organoleptic attributes of the oil samples were evaluated at all time points by a panel of tasters.…”
mentioning
confidence: 99%
“…The extra virgin olive oil (EVOO) is a typical food in which the extent and conditions of storage may affect its stability and quality. Mousavi et al [ 19 ] evaluated the effects of different conditions of storage (ambient, 4 °C and −18 °C temperatures, and argon headspace) on three EVOOs (with low, medium and high phenol contents) over 18 and 36 months, through the analyses of the main metabolites at six time points. The organoleptic attributes of the oil samples were evaluated at all time points by a panel of tasters.…”
mentioning
confidence: 99%
“…On the other hand, temperature could be easily managed during storage. Although low-temperature storage could slow down the rate of degradative phenomena, studies on the quality of VOOs stored at low or freezing temperature reported contradictory results, especially considering the fate of phenolic compounds (Cerretani et al, 2005;Li et al, 2014;Mousavi et al, 2021;Mulinacci et al, 2013). However, a study conducted on the subject has highlighted that FOOs stored under freezing conditions and the interactions between storage time and flavouring method and ingredients have been poorly investigated.…”
Section: Extraction Of Phenolic Fraction and Determination Of Phenolic Profilementioning
confidence: 99%
“…On the other hand, as supposed by Cerretani et al (2005), decrement in phenols after freezing was linked to change in the physical state of oil and the consequent solubilisation of phenols into residual water phase. Mousavi et al (2021) reported that secoiridoids (mostly 3,4-DHPEA-EDA, 3,4-DHPEA-EA and p-HPEA-EA) decreased during frozen storage, while (p-HPEA-EDA) was the most stable phenol. The findings of the present research are in partial agreement with these.…”
Section: Data Elaborationmentioning
confidence: 99%
“…Thus, modulation of gut permeability may have positive effects on glycemic control in T2DM. We and others have previously reported that in diabetic patients, intake of EVOO or its component oleuropein lowered post-prandial LPS and glycaemia, an effect of potentially clinical relevance, as post-prandial glycemia may increase the risk of cardiovascular disease [ 6 , 7 , 8 , 9 ]. However, we did not investigate the relationship, if any, between gut permeability and glycaemic control and if EVOO could improve the glycaemic profile by modulating gut permeability.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not investigate the relationship, if any, between gut permeability and glycaemic control and if EVOO could improve the glycaemic profile by modulating gut permeability. EVOO is composed of 98–98.5% triglycerides [ 6 ] and 1.5–2% of minor components such as sterols [ 7 ], fatty alcohols [ 7 ], waxes [ 8 ], phenols, tocopherols, and carotenoids [ 9 ]; furthermore, EVOO is rich in polyphenols and vitamin E [ 10 ], which could exert a beneficial effect against cardiovascular events [ 11 , 12 ] and cancer [ 13 ], even if further randomized clinical studies are necessary to confirm these hypotheses. The antioxidant property of EVOO could turn useful in the context of gut permeability, which is, in fact, enhanced by oxidative stress-mediated zonulin activation and eventually down-regulation of adhesive proteins such as tight junctions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%